Social justice pedagogies : multidisciplinary practices and approaches - Sark, Katrina (University of Toronto Press, 2023)
"Social Justice Pedagogies provides a diverse and wide perspective into making education more robust and useful in light of global injustices and new challenges posed by new media and communication practices, media manipulation, right-wing populism, climate crisis, and intersectional discriminations. Meant to inspire to see learning and teaching from a wider perspective of justice, inclusion, equity, and creativity, it argues that relational and mindful approaches to teaching and learning in specific contexts, settings, and place-based experiences, are essential in how we determine the value of education. The book draws on contributions from scholars and experts who incorporate social justice into their teaching practices in different disciplines in universities across Canada, US, and Europe. Social Justice Pedagogies uniquely presents a wide interdisciplinary perspective on social justice in education practices in order to speak to the ways in which we all want to make our research, our classrooms, and our institutions more just. It argues that pedagogy, and specifically teaching and learning, constitutes a process of building relationships between people and knowledge by fostering a learning community."--